A Transparent, High‐Performance, and Stable Sb2S3 Photoanode Enabled by Heterojunction Engineering with Conjugated Polycarbazole Frameworks for Unbiased Photoelectrochemical Overall Water Splitting Devices. Issue 29 (12th June 2022) - Wang, Lei; Lian, Weitao; Liu, Bin; Lv, Haifeng; Zhang, Ying; Wu, Xiaojun; Wang, Tuo; Gong, Jinlong; Chen, Tao; Xu, Hangxun
Abstract: Developing low‐cost, high‐performance, and durable photoanodes is essential in solar‐driven photoelectrochemical (PEC) energy conversion. Sb2 S3 is a low‐bandgap (≈1.7 eV) n‐type semiconductor with a maximum theoretical solar conversion efficiency of ≈28% for PEC water splitting. However, bulk Sb2 S3 exhibits opaque characteristics and suffers from severe photocorrosion, and thus the use of Sb2 S3 as a photoanode material remains underexploited. This study describes the design and fabrication of a transparent Sb2 S3 ‐based photoanode by conformably depositing a thin layer of conjugated polycarbazole frameworks (CPF‐TCzB) onto the Sb2 S3 film. This structural design creates a type‐II heterojunction between the CPF‐TCzB and the Sb2 S3 with a suitable band‐edge energy offset, thereby, greatly enhancing the charge separation efficiency. The CPF‐TCzB/Sb2 S3 hybrid photoanode exhibits a remarkable photocurrent density of 10.1 mA cm −2 at 1.23 V vs reversible hydrogen electrode. Moreover, the thin CPF‐TCzB overlayer effectively inhibits photocorrosion of the Sb2 S3 and enables long‐term operation for at least 100 h with ≈10% loss in photocurrent density. Furthermore, a standalone unbiased PEC tandem device comprising a CPF‐TCzB/Sb2 S3 photoanode and a back‐illuminated Si photocathode can achieve a record solar‐to‐hydrogen conversion efficiency of 5.21%, representing the most efficient PEC water splitting device of its kind. Abstract : Conformably depositing a thin layer of conjugated polycarbazole framework onto the surface of transparent Sb2 S3 thin film creates a type‐II heterojunction, leading to a transparent, high‐performance, and stable hybrid photoanode. When coupled with a bandgap‐matched back‐illuminated Si photocathode, the unbiased photoelectrochemical tandem device demonstrates an unprecedented efficiency of 5.21% toward solar‐driven overall water splitting.